Digital tools for monitoring, modeling, and supporting the life cycle of energy-adapted building solutions - SOBOL, Denis (Ways to Improve Construction Efficiency, 2025)
This paper examines modern digital tools that facilitate the management of the life cycle of energy-efficient buildings. It describes how the integration of sensor systems, cloud services, analytical platforms, and digital twins creates a unified management system that enables buildings to autonomously respond to environmental changes. Such solutions ensure continuous information exchange across all stages – from design to operation – allowing for timely detection of deviations, planning of maintenance activities, and forecasting of energy consumption. A model is proposed that integrates three core processes – monitoring, modeling, and digital support. Monitoring enables real-time tracking of technical systems, recording of indoor climate indicators, energy consumption levels, temperature, humidity, and equipment performance. Modeling allows the analysis of collected data, the development of forecasts, evaluation of energy efficiency solutions, and the creation of energy consumption scenarios that account for external factors. Digital support, in turn, ensures a continuous connection between the physical building and its virtual counterpart – the digital twin, which provides opportunities for what-if analysis and data-driven decision-making based on accurate simulations. Particular emphasis is placed on the advantages of analytical software such as Power BI, Tableau, and Qlik, which enable data integration from multiple sources, the creation of interactive control dashboards, and the visualization of complex processes in a clear and accessible format for both managers and technical specialists. Based on these tools, a Key Performance Indicator (KPI) system has been developed, encompassing energy, technical, economic, and environmental dimensions of building performance. The use of digital technologies makes it possible to transition from reactive to proactive management, where the system not only responds to events but also anticipates them. This approach helps reduce energy costs, extend equipment life cycles, enhance user comfort, and ensure the stable operation of buildings. Furthermore, it contributes to shaping a new philosophy of construction management focused on sustainability, energy conservation, and effective interaction between humans, technology, and the environment. Digital tools thus become not merely instruments of automation but the foundation of intelligent building management in the digital age.